1990
DOI: 10.1176/ajp.147.6.719
|View full text |Cite
|
Sign up to set email alerts
|

Effects of chronic cocaine abuse on postsynaptic dopamine receptors

Abstract: To assess the effects of chronic cocaine intoxication on dopamine receptors in human subjects, the authors evaluated [18F]N-methylspiroperidol binding using positron emission tomography in 10 cocaine abusers and 10 normal control subjects. Cocaine abusers who had been detoxified for 1 week or less showed significantly lower values for uptake of [18F]N-methylspiroperidol in striatum than the normal subjects, whereas the cocaine abusers who had been detoxified for 1 month showed values comparable to those obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
57
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 358 publications
(62 citation statements)
references
References 22 publications
5
57
0
Order By: Relevance
“…Non-human primates with low DA D2 receptor density show higher frequency of cocaine self-administration (Nader et al , 2006). The brain tissues of cocaine addicts show reduced D2 receptor availability via PET scan after chronic cocaine addiction (Volkow et al , 1990), and healthy volunteers with lower dopamine D2 receptor density reported liking the effects of methylphenidate (a stimulant with some structural and pharmacologic similarities to cocaine), whereas individuals with higher dopamine D2 receptor density reported more intense unpleasant effects of methylphenidate (Volkow et al , 1999). …”
Section: Discussionmentioning
confidence: 99%
“…Non-human primates with low DA D2 receptor density show higher frequency of cocaine self-administration (Nader et al , 2006). The brain tissues of cocaine addicts show reduced D2 receptor availability via PET scan after chronic cocaine addiction (Volkow et al , 1990), and healthy volunteers with lower dopamine D2 receptor density reported liking the effects of methylphenidate (a stimulant with some structural and pharmacologic similarities to cocaine), whereas individuals with higher dopamine D2 receptor density reported more intense unpleasant effects of methylphenidate (Volkow et al , 1999). …”
Section: Discussionmentioning
confidence: 99%
“…The procedures for subjects positioning and scanning protocols have been described previously [25, 28]. In short, emission scans were started immediately after injection of 4–8 mCi (specific activity 0.5–1.5 Ci/µM at end of bombardment or EOB).…”
Section: Methodsmentioning
confidence: 99%
“…These studies show that subjects with substance use disorders, compared to control subjects, have a decrease in the D 2 receptors in the striatum on the order of about 20%. The first report was in 1990, where a study showed that cocaine abuse was associated with a decrease in D 2 receptor availability in the striatum compared to controls (Volkow et al, 1990), and has been followed by a series of studies confirming this observation (Martinez et al, 2004; Martinez et al, 2011; Martinez et al, 2009; Volkow et al, 1993; Volkow et al, 1997). However, this finding is not isolated to cocaine dependence.…”
Section: Introductionmentioning
confidence: 99%